Question about SoftMath Algebrator - Algebra Homework Solver (689076614429)

Ad

**X=27**

6x-5(x-5)=52

6x-5x+25=52

x=52-25**x=27**

Posted on Jan 30, 2010

Ad

Hi,

A 6ya expert can help you resolve that issue over the phone in a minute or two.

Best thing about this new service is that you are never placed on hold and get to talk to real repairmen in the US.

The service is completely free and covers almost anything you can think of (from cars to computers, handyman, and even drones).

click here to download the app (for users in the US for now) and get all the help you need.

Good luck!

Posted on Jan 02, 2017

Ad

10+10+10=30, 10+6+6=22, 6-3+3=0, 6x(3+10)=
78

Oct 25, 2016 | Office Equipment & Supplies

Let's take 2x^2 - 10x +12 and divide it by x-2.

__2x_-_6____________

x-2 ) 2x^2 - 10x + 12

2x^2 - 4x

------------

- 6x + 12

- 6x + 12

------------

0

How many times does x go into 2x^2. Put the answer, 2x above the 2x^2. Next mulitply (x-2) by 2x and put the answer under 2x^2. Now subtract that answer from 2x^2 - 10x and we get -6x (-10x - (-4x)).

How many time does x go into -6x. -6 time. Write this above the line and put the answer above the -10x. Next multiply (x-2) by -6 and put the answer under the -6x. Subtract and we get 0 and we are done. If we want to check our answer we can multiply (x-2) and (2x - 6) and we should get 2x^2 - 10 x + 12.

Good luck.

Paul

__2x_-_6____________

x-2 ) 2x^2 - 10x + 12

2x^2 - 4x

------------

- 6x + 12

- 6x + 12

------------

0

How many times does x go into 2x^2. Put the answer, 2x above the 2x^2. Next mulitply (x-2) by 2x and put the answer under 2x^2. Now subtract that answer from 2x^2 - 10x and we get -6x (-10x - (-4x)).

How many time does x go into -6x. -6 time. Write this above the line and put the answer above the -10x. Next multiply (x-2) by -6 and put the answer under the -6x. Subtract and we get 0 and we are done. If we want to check our answer we can multiply (x-2) and (2x - 6) and we should get 2x^2 - 10 x + 12.

Good luck.

Paul

Oct 03, 2014 | Office Equipment & Supplies

x=-2

If you're asking how to do this on a particular calculator, please specify the make and mode. If this is homework, be sure to show your work.

If you're asking how to do this on a particular calculator, please specify the make and mode. If this is homework, be sure to show your work.

Feb 08, 2014 | Office Equipment & Supplies

For 3x(7x+6x)=0, x=0

For 3x(7x+6x)=1, x=1/39

For 3x(7x+6x)=2, x=2/39

For 3x(7x+6x)=3, x=3/39 or 1/13

For 3x(7x+6x)=4, x=4/39

And so on...

For 3x(7x+6x)=1, x=1/39

For 3x(7x+6x)=2, x=2/39

For 3x(7x+6x)=3, x=3/39 or 1/13

For 3x(7x+6x)=4, x=4/39

And so on...

Jun 22, 2011 | Acer Aspire One Netbook

you have to make sure you are using the correct format for your drive i.e (+/-)

8X DVD-Super Multi double-layer drive:

- Read: 24X CD-ROM, 24X CD-R, 24X CD-RW, 8X DVD-ROM, 8X DVD-R, 8X DVD+R, 8X DVD-ROM DL (double-layer), 6X DVD-R DL (double-layer), 6X DVD+R DL (double-layer), 8X DVD-RW, 8X DVD+RW, 5X DVD-RAM, 4X BD-ROM, 4X BD-R, 2X BD-RE, 4X BD-ROM DL (double-layer), 4X BD-R DL (double-layer), 2X BD-RE DL (double-layer)
- Write: 24X CD-R, 16X CD-RW, 8X DVD-R, 8X DVD+R, 6X DVD-RW, 6X DVD+RW, 5X DVD-RAM, 4X DVD+R DL (double-layer), 4X DVD-R DL (double-layer)

8X DVD-Super Multi double-layer drive:

- Read: 24X CD-ROM, 24X CD-R, 24X CD-RW, 8X DVD-ROM, 8X DVD-R, 8X DVD+R, 6X DVD-ROM DL (double-layer), 6X DVD-R DL (double-layer), 6X DVD+R DL (double-layer), 8X DVD-RW, 8X DVD+RW, 5X DVD-RAM
- Write: 24X CD-R, 24X CD-RW, 8X DVD-R, 8X DVD+R, 6X DVD-R DL (double-layer), 6X DVD+R DL (double-layer), 6X DVD-RW, 8X DVD+RW, 5X DVD-RAM

Apr 09, 2011 | Acer Computers & Internet

(2x - 3y)(3x + 2y) = 2x*3x + 2x*2y - 3y*3x - 3y*2y

= 6x^2 + 4xy - 9xy - 6y^2

= 6x^2 - 5xy - 6y^2 You multiply each element in the first set of brackets by each element in the second set of brackets and then consolidate like terms and arrange them in sequence of powers, first x and then y. So:

2x by 3x = 6x squared

2x by 2y = 4xy

-3y by 3x = -9xy

-3y by 2y = 6y squared

6x squared -5xy + 6y squared

= 6x^2 + 4xy - 9xy - 6y^2

= 6x^2 - 5xy - 6y^2 You multiply each element in the first set of brackets by each element in the second set of brackets and then consolidate like terms and arrange them in sequence of powers, first x and then y. So:

2x by 3x = 6x squared

2x by 2y = 4xy

-3y by 3x = -9xy

-3y by 2y = 6y squared

6x squared -5xy + 6y squared

Dec 04, 2010 | Yahoo Computers & Internet

The first step here is to draw a rough sketch of the two curves, and find the two points they meet. If you set x^3-6x^2+8x = x^3-4x, then you can rearrange this into the quadratic equation 6x^2-12x = 0. Solving this tells you x=0 or 2 : these are the two x values where the curves meet, and they give the bounds on your integral.

When you sketch the curves, you'll see that x^3-4x is below x^3-6x^2+8x, so the thing you need to integrate is (x^3-6x^2+8x)-(x^3-4x), that is, 12x-6x^2. If you integrate this from 0 to 2, you'll have the answer you need!

When you sketch the curves, you'll see that x^3-4x is below x^3-6x^2+8x, so the thing you need to integrate is (x^3-6x^2+8x)-(x^3-4x), that is, 12x-6x^2. If you integrate this from 0 to 2, you'll have the answer you need!

May 27, 2010 | Computers & Internet

6x+5(x+9y)+7y

6x+5x+45y+7y <- Distributive property of multiplication

11x+52y < - Simplify

11x+52y - Simplified version

Further learning:

Distributive property of multiplication:

http://www.math.unt.edu/mathlab/emathlab/distributive_property_of_multipl.htm

6x+5x+45y+7y <- Distributive property of multiplication

11x+52y < - Simplify

11x+52y - Simplified version

Further learning:

Distributive property of multiplication:

http://www.math.unt.edu/mathlab/emathlab/distributive_property_of_multipl.htm

Nov 21, 2009 | Video Game Consoles & Games

6x- 3 = y; (0, -3)

Here 6x - 3 = y is the equation

The ordered pair is (0, -3 )

It means if you substitutes 0 for x and -3 for y the equation will be true

Let us substitute and see:-

'6x' (means 6 times x) means 6 times 0 which is equal to 0

So the equation 6x - 3 = y becomes

0- 3 = -3 is correct

The ordered pair means the values of x and y which make the equation correct

Hope this is clear enough

Good luck

luciana44

Here 6x - 3 = y is the equation

The ordered pair is (0, -3 )

It means if you substitutes 0 for x and -3 for y the equation will be true

Let us substitute and see:-

'6x' (means 6 times x) means 6 times 0 which is equal to 0

So the equation 6x - 3 = y becomes

0- 3 = -3 is correct

The ordered pair means the values of x and y which make the equation correct

Hope this is clear enough

Good luck

luciana44

Sep 27, 2009 | The Learning Company Achieve! Math &...

6x+6=4x+12

Since 4x contains the variable to solve for, move it to the left-hand side of the equation by subtracting 4x from both sides.

6x+6-4x=12

Since 6x and -4x are like terms, add -4x to 6x to get 2x.

2x+6=12

Since 6 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 6 from both sides.

2x=-6+12

Add 12 to -6 to get 6.

2x=6

Divide each term in the equation by 2.

(2x)/(2)=(6)/(2)

Simplify the left-hand side of the equation by canceling the common factors.

x=(6)/(2)

Simplify the right-hand side of the equation by simplifying each term.

x=3

Good Luck

Since 4x contains the variable to solve for, move it to the left-hand side of the equation by subtracting 4x from both sides.

6x+6-4x=12

Since 6x and -4x are like terms, add -4x to 6x to get 2x.

2x+6=12

Since 6 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 6 from both sides.

2x=-6+12

Add 12 to -6 to get 6.

2x=6

Divide each term in the equation by 2.

(2x)/(2)=(6)/(2)

Simplify the left-hand side of the equation by canceling the common factors.

x=(6)/(2)

Simplify the right-hand side of the equation by simplifying each term.

x=3

Good Luck

Sep 10, 2009 | Audio Players & Recorders

99 people viewed this question

Usually answered in minutes!

×